Echoes of the Ancestors : Uncovering Bisaya Plant Wisdom in Limbang - Dilah, Tuah; Chong, Shin (Universiti Malaysia Sarawak, 2025)
A culturally significant research initiative is currently taking place in northern Sarawak to document and safeguard the traditional ethnobotanical knowledge of the Bisaya community. Supported by a special grant from the Deputy Prime Minister of Malaysia YAB Dato’ Sri Haji Fadillah bin Haji Yusof, the project represents an important contribution to the preservation of Malaysia’s intangible heritage while directly advancing several United Nations Sustainable Development Goals (SDGs), namely SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), and SDG 15 (Life on Land).